2009
DOI: 10.1007/s11524-009-9399-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Spatial Access to Pharmacies that Sell Over-the-Counter Syringes in New York City Health Districts: Relationship to Local Racial/Ethnic Composition and Need

Abstract: Pharmacies that sell over-the-counter (OTC) syringes are a major source of sterile syringes for injection drug users in cities and states where such sales are legal. In these cities and states, however, black injectors are markedly less likely to acquire syringes from pharmacies than white injectors. The present analysis documents spatial and temporal trends in OTC pharmacy access in New York City health districts over time (2001)(2002)(2003)(2004)(2005)(2006) and investigates whether these trends are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 70 publications
0
42
1
Order By: Relevance
“…Yet, spatial regressions revealed that as percent Black increased, the distance to the nearest clothing store, shoe store (general and athletic), pharmacy, health supplement store, electronics store, office supply store, and video game store increased. Cooper et al 10 surmised that perhaps chain pharmacies have less coverage of urban communities with low percentages of White residents. Our data support this assertion for several pharmacy chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, spatial regressions revealed that as percent Black increased, the distance to the nearest clothing store, shoe store (general and athletic), pharmacy, health supplement store, electronics store, office supply store, and video game store increased. Cooper et al 10 surmised that perhaps chain pharmacies have less coverage of urban communities with low percentages of White residents. Our data support this assertion for several pharmacy chains.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while racial and ethnic composition accounted for 43 % of spatial variation in access, adding poverty to the model had a negligible effect. 10 Why is the proportion of Black residents consistently inversely related to resources important for promoting and maintain health? Small and McDermott 37 contend that business operation is not based solely on customers' pockets-political and economic conditions such as government incentives and entrepreneurship grants play a key role in where and how businesses operate.…”
Section: Retail Redliningmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Spatial access to care may also mediate the relationship between residential segregation and local racial composition and breast cancer outcomes. 15,22 Predominately Black/AfricanAmerican neighborhoods tend to have poorer spatial access to health care services, [23][24][25][26][27] and increased distance and travel time to healthcare providers may be associated with less cancer treatment uptake and poorer cancer outcomes. [28][29][30][31] Here, we advance this line of inquiry by exploring the relationships between residential racial composition (RRC) and disparities in breast cancer survival in 15 metropolitan areas in Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…In New York, Cooper and colleagues conducted kernel density estimates to detect that neighborhoods with a high proportion of African American residents between 2001 and 2006 had fewer OTC syringe-selling outlets than neighborhoods with a high proportion of white residents. 31 However, little research has been conducted on the demographic and socioeconomic status (SES) factors associated with pharmacy availability and OTC syringe availability on the local level in the Western USA.…”
Section: Introductionmentioning
confidence: 99%